The clinical impact of tumour‐infiltrating lymphocytes in colorectal cancer differs by anatomical subsite: A cohort study. Issue 8 (20th July 2017) - Berntsson, Jonna; Svensson, Maria C; Leandersson, Karin; Nodin, Björn; Micke, Patrick; Larsson, Anna H; Eberhard, Jakob; Jirström, Karin
Abstract : Accumulating evidence demonstrates an association between dense infiltration of lymphocytes and prognosis in colorectal cancer (CRC), but whether this prognostic impact differs by tumour location remains unknown. This study investigated the prognostic impact of cytotoxic and regulatory T cells in CRC, with particular reference to the anatomical subsite of the primary tumour. The density of CD3 +, CD8 + and FoxP3 + tumour‐infiltrating T cells was calculated in tissue microarrays with tumours from 557 incident CRC cases from a prospective population‐based cohort. Kaplan–Meier and Cox regression analyses were applied to determine the impact of high and low lymphocyte density on 5‐year overall survival, in subgroup analysis of right colon, left colon and rectum. High CD8 + cell density was a favourable prognostic factor for patients with right‐sided colon tumours (hazard ratio [HR]=0.53, 95% confidence interval [CI] 0.29–0.95), independent of age, sex, TNM stage, differentiation grade and vascular invasion, with a significant prognostic interaction between CD8 + cells and right‐sidedness ( p  = 0.031). High FoxP3 + cell density was an independent favourable prognostic factor only in patients with rectal tumours (HR = 0.54, 95% CI 0.30‐0.99), and CD3 + cell density was an independent favourable prognostic factor for tumours in the right colon and rectum, but there was no significant prognostic interaction between CD3 + or FoxP3 + cells and sidedness. These results demonstrate that the prognostic impact of tumour‐infiltrating lymphocytes in CRC differs by primary tumour site, further indicating that tumour location may be an important factor to take into consideration in therapeutic decisions, including eligibility for immunotherapy. Abstract : What's new? In colorectal cancer, elevated levels of tumor‐infiltrating lymphocytes in the tumor and its microenvironment are associated with improved survival. Whether this prognostic benefit differs according to tumor location, however, is unknown. Here, the prognostic impacts of CD3 +, CD8 + and FoxP3 + tumor‐infiltrating T cells were examined with respect to tumor location. The data link high CD8 + density with favorable prognosis for right‐sided tumors, high FoxP3 + density to improved prognosis for rectal tumors and CD3 + density with improved prognosis for right colon and rectal tumors. Knowledge of variable immune system responses by tumor location could help inform the development of immune‐modulating therapies.